EVALUASI SISTEM MANAJEMEN KINERJA GURU DAN TENAGA KEPENDIDIKAN - Siregar , Nadia Sabrina; Tantri , Arya; Lativah, Hafni; Maulana, M. Rizki (Yayasan Amanah Nur Aman, 2024)
The performance management system for teachers and education personnel is very important to improve the quality of education in an institution. The importance of periodic evaluation of this system to find weaknesses and opportunities for professional development of educators. Currently, many educational institutions still face difficulties in implementing a comprehensive and sustainable performance management system. The purpose of this study is to determine how effective the performance management system for teachers and education personnel is in the related educational institutions. According to the results of the study, the current performance management system still has structural and procedural weaknesses. Not all performance indicators used reflect the real abilities of teachers and education personnel. Major improvements are needed in the assessment mechanism. This is especially related to more objective assessment instruments and standards. The focus of this study is on creating a more comprehensive, participatory, and competency-based performance management system model.